O ensino de gêneros do tipo descritivo: classificados e propagandas - MADEIRA, Elizete Ferreira (2024)
The present work has as its theme the teaching of descriptive genres: classifieds and advertisements. The general objective of the work is to develop, in students, reading and writing skills of descriptive genres. To achieve this objective, we seek to understand the social functions of classified genres and advertisements, to know the formal characteristics of classifieds and advertisements, to understand the discursive value of the textual type description in classifieds and advertisements, and to know how to produce a descriptive text based on the studied genres. . The theoretical framework is based on the interactionism proposed by ANTUNES (2009), on the guidelines of the PCN of Portuguese language for secondary education (2006), on the definition of Bakhtin (2000) on the genre of speech, on the conceptions of types of texts by Marcuschi (n.d) and in the conceptions of Dolz, Norrevaz and Schneuwly (2004) about didactic sequence. With this, the student is expected to develop the ability to read and write classified genres and advertisements, understand the social functions of these genres and develop the set of creation and recreation skills required in the construction of classifieds and advertisements.